Seasonal differences in energy expenditure, flight characteristics and spatial utilization of Dalmatian Pelicans Pelecanus crispus in Greece - Efrat, Ron; Harel, Roi; Alexandrou, Olga; Catsadorakis, Giorgos; Nathan, Ran (My University, 2019)
Animals typically adjust their behaviour to their changing environment throughout the annual cycle, modulating key processes such as the timing of breeding and the onset of migration. Such behavioural changes are commonly manifested in the movements and the energetic balance of individuals in relation to their species‐specific physiological characteristics, habitat attributes and the environmental properties of their distribution ranges. We used GPS and acceleration data collected using transmitters on free‐ranging birds to quantify annual movement patterns and estimate energy expenditure of the Dalmatian Pelican Pelecanus crispus, a large, soaring avian species which performs short‐distance migration and spends its entire annual cycle in mid‐latitudes. To assess the representativeness of our results, the transmitter effect was also tested. We found that daily trends in the overall dynamic body acceleration (ODBA; a proxy for energy expenditure) differed among seasons, with the highest values occurring during spring and the lowest during winter. Long inter‐lake flights were very rare in winter, and the number of flights and ODBA during spring was higher than during summer, suggesting greater motivation to move in spring. Although transmitters may have affected the birds, as none of the tagged birds bred, we found seasonal differences in behaviour and activity level. The observed patterns in differences in activity levels, long‐distance flights and flight characteristics between seasons suggest an annual rhythm of energy expenditure. These findings allow a better understanding of bird phenology, specifically regarding adaptations to wintering in a cold climate by reducing movement‐driven energy expenditure. Finally, the identification of periods with high and low energy expenditure may guide future conservation efforts by adjusting conservation plans in accordance with changing needs during the annual cycle.
Keywords: annual cycle, movement, short‐distance migration, soaring; 570